Mutational analysis of an antimalarial drug target, Pf ATP4 - Swaksha Rachuri; Binod Nepal; Anurag Shukla; Aarti Ramanathan; Joanne M. Morrisey; Thomas Daly; Michael W. Mather; Lawrence W. Bergman; Sandhya Kortagere; Akhil B. Vaidya (Proceedings of the National Academy of Sciences, 2025)
Among new antimalarials discovered over the past decade are multiple chemical scaffolds that target Plasmodium falciparum P-type ATPase ( Pf ATP4). This essential protein is a Na + pump responsible for the maintenance of Na + homeostasis. Pf ATP4 belongs to the type 2D subfamily of P-type ATPases, for which no structures have been determined. To gain better insight into the structure/function relationship of this validated drug target, we generated a homology model of Pf ATP4 based on sarco/endoplasmic reticulum Ca 2+ ATPase, a P2A-type ATPase, and refined the model using molecular dynamics in its explicit membrane environment. This model predicted several residues in Pf ATP4 critical for its function, as well as those that impart resistance to various Pf ATP4 inhibitors. To validate our model, we developed a genetic system involving merodiploid states of Pf ATP4 in which the endogenous gene was conditionally expressed, and the second allele was mutated to assess its effect on the parasite. Our model predicted residues involved in Na + coordination as well as the phosphorylation cycle of Pf ATP4. Phenotypic characterization of these mutants involved assessment of parasite growth, localization of mutated Pf ATP4, response to treatment with known Pf ATP4 inhibitors, and evaluation of the downstream consequences of Na + influx. Our results were consistent with modeled predictions of the essentiality of the critical residues. Additionally, our approach confirmed the phenotypic consequences of resistance-associated mutations as well as a potential structural basis for the fitness cost associated with some mutations. Taken together, our approach provides a means to explore the structure/function relationship of essential genes in haploid organisms.